Literarni zgodovinar Karel Štrekelj - Dolinar, Darko (Slavistična revija, 2013)
Karel Štrekelj, a classic of Slovene ethnography and one of the more prominent philologists, also contributed to Slovene literary history. His main contributions to this discipline are lectures for the course he gave at the University of Graz in 1899-1901, which were never published and fell into oblivion. This article comments on the circumstances that accompanied the compilation of the course, describes its content, and provides a detailed analysis of Štrekelj's definition of literary history as a discipline and his selection of methodology. Base on this it charactarizes Štrekelj's approach, which is marked by objective historicism, and determines its place on the timeline of the discipline's development.
Keywords: filologija; history of literature; Literarna zgodovina; literarni zgodovinarji; literary historian; literary historians; literary history; philology; Slavic studies; slavistika; Slovene literature; slovenska književnost; Štrekelj, Karel, 1859-1912